Analisis Dampak Sektor Pariwisata terhadap Kesejahteraan Pedagang di Kota Banjarmasin - Kristo Kristo; Yunita Sopiana (PPJP Universitas Lambung Mangkurat, 2020)
This study was conducted to (1) analyze the impact of the tourism sector on the welfare of traders in the tourist area of the Siring Sungai Martapura Park in the City of Banjarmasin (2) to analyze the differences in the welfare level of traders who utilize the tourism sector before and after the development of tourism in the tourism area of the Siring River Martapura Park Banjarmasin City. In this study, Respondents were 38 people, namely traders who are still active around the Siring Sungai Martapura Park in Banjarmasin City. This research is a qualitative descriptive study. In this study, data collection methods were interviews in the form of cake, observation, documentation, and literature study. The results of this study prove the positive impact of the tourism sector on the welfare of traders around the Banjarmasin tourist attraction used in this study, namely the Siring Sungai Martapura Park Banjarmasin City viewed from the tourism sector which gives an impact on increasing income before and after the development of tourism, education level, the level of health, and living conditions that indicate merchants who have increased welfare before and after utilizing the tourism sector. The resulting negative impact is the dependence on the existing tourism sector because it depends on tourist visits. The tourism sector is used as an indicator in the study. This is a tourist visit while public welfare indicators are income, expenditure, health, education, and living conditions.